Pemetaan Emosi Dominan pada Kalimat Majemuk Bahasa Indonesia Menggunakan Multinomial Naïve Bayes - Wisnu Agastya; Aripin (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
This study aimed at mapping Indonesian sentences into emotion classes based on the classification process in those sentences. The results of emotion mapping can be applied in various fields, such as production of animated films and games, analysis of facial expressions, human-computer interactions, and development of other expressive virtual characters, specifically to produce facial expressions that match the spoken sentences. The method used for the emotion mapping process was the text classification using multinomial naïve Bayes model that was accompanied by dominant boundary equation. Multinomial naïve Bayes model in the text classification is used to determine the types and the emotional intensity of Indonesian sentences, whereas dominant boundary equation iss used to determine the threshold in order to identify the dominant classes. The emotion classes used as references are six basic emotion classes according to Paul Ekman, i.e., happiness, sadness, anger, fear, disgust, and surprise. The experiment on the process of mapping emotions used Indonesian single and compound sentences. The experimental results show that the text classification using multinomial naïve Bayes model accompanied by dominant boundary equation can map compound sentences into several classes of dominant emotions.